Digital tourism communication: effects of influencer credibility, content quality, and e-WoM on emotions, FoMO, self-identification, and visit intentions of Gen Z travelers - Widaningsih, Themotia Titi; Putranto, Algooth (Frontiers in Communication, 2025)
IntroductionThe rapid expansion of short-video platforms has transformed destination promotion, yet the psychological processes linking digital stimuli to behavioral intentions among young travelers remain underexplored.MethodsUsing the Stimulus-Organism-Response (S-O-R) framework and a Partial Least Squares Structural Equation Modeling (PLS-SEM) approach, data were collected from 344 Generation Z respondents aged 21-27 years who had previously viewed Bali-related content on TikTok.ResultsThe analysis reveals two main pathways: a direct effect of Influencer Credibility, TikTok Content Quality, and Electronic Word of Mouth on behavioral responses (β = 0.417), and an indirect path through the psychological Organism-Emotion, Fear of Missing Out (FoMO), and Self-Identification which also significantly influences responses (β = 0.149). TikTok Content Quality emerged as the most dominant stimulus (β = 0.760), while Self-Identification was the strongest psychological predictor within the Organism construct (β = 0.785). Intention to Visit showed the highest loading within the Response construct (β = 0.889), indicating the strong persuasive power of digital content.DiscussionAlthough the model demonstrates high reliability at the lower-order construct level, limitations in convergent and discriminant validity were identified in higher-order constructs. The study extends the S-O-R framework in algorithm-driven short-video contexts and offers practical insights for tourism boards and digital strategists seeking to enhance cultural engagement and increase destination visit intentions among young travelers.